Innovation and Strategy of Madrasah Ibtidaiyah Teachers in Implementing the Independent Curriculum - Rahayu, Tina; Muhroji, Muhroji; Aflahah, Noor Aida; Fath, Muhammad Sandy Al (Jurnal Ilmiah Kampus Mengajar, 2024)
The aim of the research is to describe teachers' readiness to implement the independent curriculum at the MI Muhammadiyah Kartasura Special Program. This research is descriptive and qualitative. The data collection techniques used were observation, interviews, and documentation. Data validity using source triangulation techniques. And the data analysis used is an interactive analysis model with stages of data collection, data reduction, data presentation, and drawing conclusions. The research results show that teachers are ready to implement the independent curriculum. There are five aspects that have been carried out by teachers before implementing the independent curriculum in the learning process, namely readiness in understanding the curriculum structure, readiness to plan learning, learning process readiness, teaching module readiness, and learning assessment readiness.